USE OF GEOSTATISTICS ON ABSOLUTE POSITIONAL ACCURACY ASSESMENT OF GEOSPATIAL DATA - Santos, Alex da Silva (2017)
In the area of Geosciences it is intuitive to think of spatial correlation as a phenomenon under study, and Geostatistics has tools to identify and represent the behavior of such dependency. The spatial analysis of the results of an inspection of the quality of a cartographic product is generally not addressed in the standards, which are restricted to descriptive and tabular findings, based on the assumption of the Classical Statistics of independence of observed data. At the Brazilian National Infrastructure of Spatial Data (INDE), various cartographic products should be made available to society, along with their metadata. This paper proposes a methodology for quality inspection based on international standards and on the Cartographic Accuracy Standard (PEC), using geostatistical methods and spatial representation of this benchmarking, through positional quality maps. The method of evaluating the quality of data was applied to Brazil's Continual Cartographic Base, at the scale of 1:250000 - BC250, with a focus on absolute positional accuracy. The quality map generated presented regionalizations of the planimetric error confirmed by the producer team of the referred cartographic base of IBGE. Such information can help users and producers to understand the spatial behavior of cartographic product quality in study.